Pelatihan Penguatan Profil Pelajar Pancasila: Bergotong Royong dengan Tema Team Building Murid-Murid SMP Maitreyawira Deli Serdang - Sutarno, Sutarno; Anggraini, Dewi; Ciamas, Elserra Siemin (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Educational transformation through the Kurikulum Merdeka demands the strengthening of student character, particularly in the